1 Recent Technological Developments In Deep Foundations With Soil Excavation - Deep Foundations With Soil Excavation: Bored Piles, Root Piles, CFA Piles, Slurry Trench Walls - Allocation Of papers - J. Hartikainen (Deep Foundations Institute, 1994)
19 papers were allocated to this session by the paper classification committee, 8 related to bored piles, 5 to continuous flight auger piles (CFA piles), 3 to slurry trenches, 2 to both bored piles and slurry trenches, one of them also dealing with root piles. There were no papers dealing with root piles only, as root filling is a different technique. One paper concerns sheet piling (Table 1). Table 1. Papers for session 1: Recent Technological Developments in Deep Foundations with Soil Excavation. [ ] Table 2. Classification of pile type in Belgium - van Impe W.F. /10/. [ ] Trends in piling Trends in piling in Central Europe were studied by van Impe for his brilliant lecture to the Finnish Civil Engineering Society. He claimed that bored piling is on the decrease and CFA pilling on the increase (Table 2). Thus the numbers of papers presented here do not conform to recent developments or trends. The papers submitted arc of course influenced largely by the fact, observable in Table 3, that bored piling is